2022
DOI: 10.2147/ijgm.s381188
|View full text |Cite
|
Sign up to set email alerts
|

ESPL1 is Elevated in Hepatocellular Carcinoma and Predicts Prognosis

Abstract: The extra spindle pole bodies-like 1 (ESPL1) gene is associated with malignant biological behaviors in several tumors. Nevertheless, the correlation between hepatocellular carcinoma (HCC) and ESPL1 has not been determined. The present study analyzed the molecular function and prognostic value of ESPL1 in HCC. Patients and Methods: Samples from 121 HCCs and 119 adjacent normal tissue specimens were subjected to next-generation sequencing. Clinicopathological and genetic data of HCC patients in The Cancer Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that ESPL1 is highly expressed in various tumours. Song et al [ 11 ] showed that ESPL1 expression was upregulated in HCC and substantially increased the mortality rate of HCC patients. Liu et al [ 30 ] suggested that the high expression of ESPL1 promoted the proliferation, migration and apoptosis of LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that ESPL1 is highly expressed in various tumours. Song et al [ 11 ] showed that ESPL1 expression was upregulated in HCC and substantially increased the mortality rate of HCC patients. Liu et al [ 30 ] suggested that the high expression of ESPL1 promoted the proliferation, migration and apoptosis of LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that ESPL1 participates in cell cycle signalling in breast cancer [ 32 ], endometrial cancer (UCEC) [ 33 ] and HCC [ 11 ], thus promoting the proliferation and migration of cancer cells [ 14 ]. However, in terms of BC, the potential pathways in which ESPL1 is involved still need to be better defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 38 ] Overexpression or aberrant activation of ESPL1 can lead to aneuploidy and chromosomal instability, which are hallmarks of cancer. Research has shown that ESPL1 is involved in the development and progression of several types of cancer, including glioma, [ 39 ] breast, [ 40 ] stomach, [ 41 ] bladder, [ 42 ] liver, [ 43 ] and endometrial [ 44 ] cancers. HJURP is a protein-coding gene that plays a crucial role in centromere function and chromosomal stability by facilitating the assembly of the CENP-A nucleosome at centromeres.…”
Section: Discussionmentioning
confidence: 99%